Models in Software Engineering Workshops and Symposia at MODELS 2010, Oslo, Norway, October 2-8, 2010, Reports and Revised Selected Papers - Dingel, Juergen; Solberg, Arnor; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book presents a comprehensive documentation of the scientific outcome of 14 satellite events held at the 13th International Conference on Model-Driven Engineering, Languages and Systems, MODELS 2010, held in Oslo, Norway, in October 2010. Besides the 21 revised best papers selected from 12 topically focused workshops, the post-proceedings also covers the doctoral symposium and the educators symposium; each of the 14 satellite events covered is introduced by a summary of the respective organizers. All relevant current aspects in model-based systems design and analysis are addressed. This book is the companion of the MODELS 2010 main conference proceedings LNCS 6394/6395.
Keywords: Computer science; Software engineering; Logic design; Computer simulation; Information Systems; Computer Science; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Management of Computing and Information Systems; Simulation and Modeling